The Nile delta as a centre of cultural interactions between upper Egypt and the southern Levant in the 4th millenium BC: [proceedings of the conference held in the Poznan Archaeological Museum, Poznań, Poland, 21 - 22 June 2013] - Mączyńska, Agnieszka (Studies in African archaeology, 2014)
Literaturangaben